-15=-5h+2/5(40-3h)

Simple and best practice solution for -15=-5h+2/5(40-3h) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15=-5h+2/5(40-3h) equation:


h in (-oo:+oo)

-15 = (2/5)*(40-(3*h))-5*h // - (2/5)*(40-(3*h))-5*h

-((2/5)*(40-(3*h)))-(-5*h)-15 = 0

(-2/5)*(40-3*h)+5*h-15 = 0

5*h-2/5*(40-3*h)-15 = 0

5*h-2/5*(40-3*h)-15 = 0

31/5*h-16-15 = 0

31/5*h-31 = 0

31/5*h-31 = 0

31/5*h-31 = 0 // + 31

31/5*h = 31 // : 31/5

h = 31/31/5

h = 5

h = 5

See similar equations:

| 2(5x-8)=(10*x)-16 | | 8m+7+m=28 | | 8m+7+m=18 | | -8-7(y+3)= | | -x/3+10=19 | | 3(x-1)=-3x+45 | | 16h=16h+-80 | | -5x^3+5x=0 | | f-3fg+2g-fg+1= | | x/2-3/4=1/2 | | t/-3=15 | | 3*3-2y=-7 | | B+7=5b+15 | | -4+1/2x=-5 | | 1/3w=-5 | | 5(3x-9)=45 | | 1/2a=-9 | | 10+28/2-6= | | 9+5y=14 | | x/5-1=9 | | 9x+3x=11x | | 84+7m=196 | | 2n+6=5n-9 | | 6z+4z=9z+2 | | 23n-140=182 | | -10x^2+60x=0 | | 6m+5.25=50.25 | | (6*x^17*y^12)/(2*x^16*y^10) | | 9x+34=-8x | | n/10+3=10 | | (6x^17*y^12)/(2x^16*y^10) | | 3+5+6=94 |

Equations solver categories